Transition form factors of the $$Λ _b → Λ (1520)$$ Λ b → Λ ( 1520 ) in QCD light-cone sum rules - Ke-Sheng Huang; Hua-Yu Jiang; Fu-Sheng Yu (European Physical Journal C: Particles and Fields, 2025)
Abstract In this work, we investigate the transition form factors for $$Λ _b→ {Λ (1520)}$$ Λ b → Λ ( 1520 ) within the framework of light-cone sum rules (LCSR), using the light-cone distribution amplitudes (LCDAs) of the $$Λ _b$$ Λ b -baryon. In the hadronic representation of the correlation function, we carefully select the appropriate Lorentz structures and isolate the contributions from both the $$Λ (1520)(J^P=(3/2)^-)$$ Λ ( 1520 ) ( J P = ( 3 / 2 ) - ) and the $$Λ (1890)(J^P=(3/2)^+),$$ Λ ( 1890 ) ( J P = ( 3 / 2 ) + ) , ensuring that the form factors for $$Λ _b→ {Λ (1520)}$$ Λ b → Λ ( 1520 ) can be calculated unambiguously. We also provide predictions for various physical observables in the decay $$Λ _b→ {Λ (1520)}l^+l^-,$$ Λ b → Λ ( 1520 ) l + l - , including the differential branching fraction, the lepton-side forward–backward asymmetry, the longitudinal polarization fraction, and the CP-averaged normalized angular observable. Our prediction for the differential branching fraction of $$Λ _b→ {Λ (1520)}μ ^+μ ^-$$ Λ b → Λ ( 1520 ) μ + μ - is in good agreement with the LHCb measurement within the uncertainties.